"Look, an Illegal Alien!": the rhetorics of migrant "Illegality" and the racialization of Mexicanness. Issue 1 (2nd January 2023) - Genova, Nicholas De
ABSTRACT: There is a sociopolitical and juridical regime that I have designated in terms of "the legal production of Mexican/migrant 'illegality', " which is never separable from a larger discursive formation of migrant "illegality, " which has always also been constitutive to the (re-)racialization of "Mexican"-ness in the United States. As a scholar of rhetoric, Lisa Flores amplifies and illuminates these multiple dimensions of the rhetoricity of race, national identity, and citizenship. By examining this succession over the first half of the twentieth century of "moments of rhetorical crisis" surrounding the mass-mediated and highly politicized spectacles that produced "Mexicans" as "problem, " Flores critically demonstrates how U.S. public discourse has named "Mexicans" and called upon the public to see "Mexicans" — variously, as "illegal aliens, " "zootsuiters, " braceros, and "wetbacks" — such that the law and law enforcement, politics and policing, as well as mass-mediated public discourse have been indispensable for the ensnaring of "Mexicanness" within deportability and disposability and confining "Mexicans, " both migrants and U.S.-born ostensible citizens, within a regime of racial subordination.